Intensity-Based Rebating of Emission Pricing Revenues - Böhringer, Christoph; Fischer, Carolyn; Rivers, Nicholas (World Bank, Washington, DC, 2022)
Carbon pricing policies worldwide are increasingly coupled with direct or indirect subsidies where emissions pricing revenues are rebated to the regulated entities. This paper analyzes the incentives created by two novel forms of rebating that reward additional emission intensity reductions: one given in proportion to output (intensity-based output rebating) and another that rebates a share of emission payments (intensity-based emission rebating). These forms are contrasted with output-based rebating, abatement-based rebating, and lump sum rebating. Given the same emission price, intensity-based output rebating incentivizes the most intensity reductions, while abatement-based rebating incentivizes the most output reductions, and output-based rebating puts the least pressure on output (and emissions); intensity-based emissions rebating lies in between these, by implicitly subsidizing emissions while incentivizing intensity reductions. The paper supplements partial equilibrium theoretical analysis with numerical simulations to assess the performance of different mechanisms in a multisector general equilibrium model that accounts for economywide market interactions.